2014
DOI: 10.1007/s11605-014-2671-5
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in Bile Duct Injury: 1-, 5-, and 10-year Outcomes After Surgical Repair

Abstract: Quality of life improves significantly after the first year of surgical repair, reaching a plateau at 5 years. No correlation exists with physician-centered outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 14 publications
0
10
0
2
Order By: Relevance
“…Although BDIs have been consistently classified using Strasberg classification for nearly two decades, the outcome reporting has not been standardized much due to the lack of uniform agreement on the grading of various outcomes and this has led to difficulties in comparing different series to one another [ 10 , 14 ]. Moreover, the effect of BDI on quality of life (QOL) has been controversial, which might stem from lack of standardized outcome reporting [ 15 21 ].…”
mentioning
confidence: 99%
“…Although BDIs have been consistently classified using Strasberg classification for nearly two decades, the outcome reporting has not been standardized much due to the lack of uniform agreement on the grading of various outcomes and this has led to difficulties in comparing different series to one another [ 10 , 14 ]. Moreover, the effect of BDI on quality of life (QOL) has been controversial, which might stem from lack of standardized outcome reporting [ 15 21 ].…”
mentioning
confidence: 99%
“…While there are numerous publications on BDIs, only 12 have investigated HRQoL after BDI. 16,[28][29][30][31][32][33][34][35][36][37][38] Assessing HRQoL is important and relevant as this quantifies the impact and consequences of a BDI from the patient's perspective, reflects self-perception of well-being and considers functionality or relief of a particular symptom, emotional status, social role, and mental health. 39 Previous studies on HRQoL outcome after BDI have reported discordant results, with some showing no difference between LC-BDI patients and those who had an uneventful LC, while others report significant long-term reductions in both physical and mental HRQoL.…”
Section: Perspectivementioning
confidence: 99%
“…40 This discordance may be due to underpowered designs, sample selection, selection bias and inclusion of heterogeneous populations treated with either endoscopy, interventional radiology or surgery. 31 In the first detailed analysis of the impact of LC-BDI on HRQoL, the Amsterdam group used the Short Form 36 Health Survey ® (SF-36) and reported worse physical and mental HRQoL compared to an uncomplicated LC cohort and average general population values. 30 These findings were later replicated in an expanded sample by the same group and were similar to a report from Moore et al, showing worse SF-36 physical and mental HRQoL in BDI patients compared with LC patients.…”
Section: Perspectivementioning
confidence: 99%
“…Quality of life improves significantly after the first year of surgical repair, reaching a plateau at five years [14]. With a minimum of five years of follow-up, the QoL after surgical biliary reconstruction compares favorably with that of patients undergoing uneventful cholecystectomy [15].…”
Section: Research Article Peer Reviewed | Open Access Wwwijhpdcommentioning
confidence: 99%